Effects of drying on the nutritional, sensory and microbiological quality of edible stinkbug (Encosternum delgorguei) - Melania Dandadzi; Robert Musundire; Alice Muriithi; Ruth T. Ngadze (Heliyon, 2023)
Entomophagy has recently gained attention as a potential solution to the problems of food and nutritional security. One example is the consumption of edible stinkbug. Different drying techniques may affect the nutritional, microbiological and sensory properties of the edible stinkbugs. Thus, the study assessed the effects of toasting, microwave, oven and sun drying on the nutritional composition, microbiological quality and sensory attributes of processed edible stinkbugs. Drying significantly (p < 0.05) increased the crude protein and fat content of the edible stink bugs with the highest values being recorded for the toasted samples (66.65 & 37.17% respectively). Highest Ca, K, Zn, Mg, Fe and P values were recorded after microwave drying. Reduction of 2.94 and 2.99 log cycles of the total viable count (TVC) was observed in oven and microwave dried edible stinkbugs. Toasting and microwave drying eliminated the yeasts and moulds, Enterobacteriaceae and lactic acid bacteria (LAB) in edible stinkbugs. The appearance, aroma, taste, texture and overall acceptability scores were in the same order for toasted > oven dried > microwave dried > sun dried edible stinkbugs. Toasting, oven and microwave drying can be used for processing of edible stinkbugs.